A Survey on Big Data: Technologies, Trends and Tools - Sarika A. Panwar; Pallavi S. Deshpande (AG Volumes, 2022)
Data sets which are too huge or complicated for typical data processing tools, such as relational databases, are referred to as "big data." From the outset, big data has been at the core of companies such as Ebay, Google, LinkedIn, and Fb. Massive as well as complicated data sets, including social media analytics as well as data management skills, as well as real-time data, are included within the collection. The complexity of big data necessitates the development of new methods, algorithms, and analytics for their management and analysis, as well as for their value creation and information extraction. The primary goal of this article is to provide an overview of the current status of Big Data research. In addition, we’ll talk about the latest in technology as well as tools, as well as potential problems and emerging trends.